2016
DOI: 10.1117/1.jatis.2.4.041209
|View full text |Cite
|
Sign up to set email alerts
|

Technology gap assessment for a future large-aperture ultraviolet-optical-infrared space telescope

Abstract: The Advanced Technology Large Aperture Space Telescope (ATLAST) team identified five key technology areas to enable candidate architectures for a future large-aperture ultraviolet/optical/ infrared (LUVOIR) space observatory envisioned by the NASA Astrophysics 30-year roadmap, "Enduring Quests, Daring Visions." The science goals of ATLAST address a broad range of astrophysical questions from early galaxy and star formation to the processes that contributed to the formation of life on Earth, combining general a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 34 publications
(50 reference statements)
1
29
0
Order By: Relevance
“…The roadmap technologies are consistent with the more detailed description developed by Bolcar et al 43 for the ATLAST concept described in Sec. 2: precision deployment and wavefront control, mirror coatings, detector systems, andvery critically-high-performance starlight suppression.…”
Section: The Nasa Astrophysics Roadmap: Vision For the Next Three Decsupporting
confidence: 65%
See 1 more Smart Citation
“…The roadmap technologies are consistent with the more detailed description developed by Bolcar et al 43 for the ATLAST concept described in Sec. 2: precision deployment and wavefront control, mirror coatings, detector systems, andvery critically-high-performance starlight suppression.…”
Section: The Nasa Astrophysics Roadmap: Vision For the Next Three Decsupporting
confidence: 65%
“…Our ATLAST study was concluded in late 2015 with study results passed on to the current Large UV/Optical/ IR (LUVOIR) Surveyor assessment. Our ATLAST design reference mission is reported on in additional detail elsewhere by Bolcar et al 43 and Rioux et al 45 The remainder of this paper gives an overview of the design, including the strategy pursued in its development.…”
Section: Association Of Universities For Research Inmentioning
confidence: 99%
“…The two main areas of technology development for the LUVOIR concept are 1) the ultra-stable optomechanical structure required to form a large primary mirror out of segments, with the required picometer-class wavefront error stability, and 2) segmented-aperture coronagraphy at the 10 −10 contrast level. 57 For the former challenge, the team is building on experience gained from the ATLAST 9 m telescope study 38 which had a similar architecture to designs under consideration for LUVOIR. The LUVOIR team is performing model-based analysis to show that the wavefront error requirement can be met, and to broadly flow requirements into different subsystems with multiple levels of open and closed-loop control.…”
Section: Luvoirmentioning
confidence: 99%
“…1 shows the detector requirements that were used for NASA's recently completed ATLAST study. 7 We adopt these as the basis for further discussion. We are aware of additional desirable characteristics.…”
Section: Strawman Detector Needsmentioning
confidence: 99%
“…For other science programs, a general purpose LUVOIR would benefit from better detectors across its full 90 nm − 2.5 µm "stretch" wavelength range, including the UV. We refer the interested reader to Bolcar et al,7 for a discussion of some of these other detector needs 4. These longer wavelength lines would present other challenges, including reduced angular resolution (for a fixed aperture) and potentially increased thermal background.…”
mentioning
confidence: 99%